Development of an Approach to Automate Performance Evaluation of Bank Staff by Internal Audit Using Excel Program (Al-Mansour Journal, 2022)
Banks perform activities affecting directly the society; this requires the imposition of an efficient, effective and sustainable control on its activities. Control imposition relies basically on the internal control department. Internal auditing is an independent, objective assurance and consulting activity that adds value and improves an economic unit’s operations. This paper aims at shedding light on contemporary developments taking place in the internal audit, with proposing an approach calls for making use of general application program such as Microsoft Excel in monitoring and evaluating the performance, and as a step towards applying Computer Auditing Assisting Techniques (CAATs). Conclusions of most importance are: (1) Microsoft Excel can be used as a preliminary step to adopt (CAATs), by utilizing the program’s functions in the accumulation and analysis of audit data, documentation of results. (2) Sortingand classifying errors according to their risk impact into serious, influential, and small, translating these classes to values, makes the evaluation more objective. (3) The evaluation is characterized by its efficiency and effectiveness. (4) Using the approach helps to direct management and audit committee attention toward providing assurances about controls.
Keywords: Performance Evaluation; Internal Audit; Microsoft Excel; Audit Committee; Computer Auditing Assisting Techniques